Association between Labeobarbus spp. (Teleostei: Cyprinidae) and environmental variables in the Luhoho basin (Eastern Congo River basin; DRC). Issue 2 (28th March 2021) - Kisekelwa, Tchalondawa; Snoeks, Jos; Zamba, Armel Ibala; Amzati, Gaston Sefu; Isumbisho, Mwapu; Masilya, Pascal Mulungula; Lemmens, Pieter; Vreven, Emmanuel
Abstract: The African cyprinid genus Labeobarbus is characterized by a high polymorphism in mouth morphology. The association between four species of this genus (two chiselmouths, one rubberlip with a well‐developed fleshy mental lobe on the lower jaw, i.e ., a fleshy appendage on the chin, and one usually with a poorly developed one) and 26 environmental variables was investigated in four affluents of the Luhoho River in the Albertine Highlands of the Upper Congo basin. A combination of univariate and multivariate analyses suggested that differences exist in habitat composition at localities where different Labeobarbus species were reported, and within different mouth phenotypes. The association of L. longidorsalis with the presence of cobbles and pebbles and of L. brauni with the presence of boulders suggests that the occurrence of chiselmouths phenotype is associated with stony habitats, whereas phenotypes with a mental lobe, i.e ., Labeobarbus longifilis and L. paucisquamatus, mostly occupy habitats without stones. Differences in the distribution between these two species appear to be linked to physico‐chemical parameters such as electrical conductivity and water temperature rather than substrate type. The findings of this study are relevant for developing guidelines that aim effective local preservation and conservation of these Labeobarbus species.